Measurement of the B- and (B)over-bar(0) meson lifetimes using semileptonic decays - Abe, F; Akimoto, H; Akopian, A; Albrow, MG; Amendolia, SR; Amidei, D; Antos, J; AnwayWiese, C; Aota, S; Apollinari, G; Asakawa, T; Ashmanskas, W; et al. (1996)
The lifetimes of the B- and B̄0 mesons are measured using the partially reconstructed semileptonic decays B̄ → Dℓ-v̄X, where D is either a D0 or D*+ meson. The data were collected by the CDF detector at the Fermilab Tevatron collider during 1992-1993 and correspond to 19.3 pb-1 of pp̄ collisions at √s = 1.8 TeV. We measure the decay length distributions and find the lifetimes to be τ(B-) = 1.56 ± 0.13 ± 0.06 ps and τ(B-0) = 1.54 ± 0.08 ± 0.06 ps, and the ratio of lifetimes to be τ(B-)/τ(B-0) = 1.01 ± 0.11 ± 0.02, where the first uncertainties are statistical and the second are systematic.